Real‐world clinical, endoscopic and radiographic efficacy of vedolizumab for the treatment of inflammatory bowel disease. Issue 6 (31st July 2018) - Kotze, Paulo G.; Ma, Christopher; Almutairdi, Abdulelah; Al‐Darmaki, Ahmed; Devlin, Shane M.; Kaplan, Gilaad G.; Seow, Cynthia H.; Novak, Kerri L.; Lu, Cathy; Ferraz, Jose G. P.; Stewart, Michael J.; Buresi, Michelle; et al.
Summary: Background: Vedolizumab is an α4β7 integrin antagonist with proven efficacy for inducing and maintaining clinical response and remission in Crohn's disease (CD) and ulcerative colitis (UC). Aim: To evaluate clinical and objective response and remission rates with vedolizumab in a large, real world cohort. Methods: A retrospective cohort study of adult CD and UC patients receiving vedolizumab between 2012 and 2017 was conducted. Primary outcome: clinical or objective response and remission at 3, 6 and 12 months after induction. Clinical remission was defined by complete, steroid‐free absence of symptoms. Objective remission was defined by endoscopic mucosal healing or normalisation of radiographic appearance on contrast‐enhanced ultrasound or CT/MR enterography. Results: The study included 222 vedolizumab patients (122 CD, 100 UC). In CD, clinical remission at 3, 6 and 12 months was achieved in 19.8% (22/111), 22.1% (21/95) and 22.1% (15/68) of patients, respectively. Objective remission occurred in 11.5% (6/52), 21.2% (14/66), and 18.9% (7/37) of patients at 3, 6 and 12 months, respectively. In UC, clinical remission at 3, 6, and 12 months was 51.0% (51/100), 61.8% (55/89) and 61.9% (39/63), respectively. Endoscopic remission occurred in 27.5% (11/40), 41.0% (16/39) and 47.8% (22/46) of patients at 3, 6 and 12 months, respectively. In multivariable analysis, patients with UC as compared to CD, and those with milder disease activity were more likely to achieve objectively defined remission at both 6 and 12 months. Conclusions: Vedolizumab was effective for induction and maintenance of clinical and objective remission, both in Crohn's disease and ulcerative colitis.